Work organization and high-paying jobs - Dylan Nelson; Nathan Wilmers; Letian Zhang (W.E. Upjohn Institute for Employment Research, 2024)
High-paying factory jobs in the 1940s were an engine of egalitarian economic growth for a generation. Are there alternate forms of work organization that deliver similar benefits for frontline workers? Work organization varies by type of complexity and degree of employer control. Technical and tacit knowledge tasks receive higher pay for signaling or developing human capital. Higher-autonomy tasks elicit efficiency wages. To test these ideas, we match administrative earnings to task descriptions from job postings. We then compare earnings for workers hired into the same occupation and firm, but under different task allocations. When jobs raise task complexity and autonomy, new hires' starting earnings increase and grow faster. However, while half of the earnings boost from complex, technical tasks is due to shifting worker selection, worker selection changes less for tacit knowledge tasks and very little for adding high-autonomy tasks. We also study which employers provide these jobs: frontline tacit knowledge tasks are disproportionately in larger, profitable manufacturing and retail firms; technical tasks are in newer health and business services; and higher-autonomy jobs are in smaller and fast-growing firms. These results demonstrate how organization-level allocations of tasks can undergird high-paying jobs for frontline workers.
Keywords: J24; J31; M54; 330; Wage level and structure; wage differentials; human capital; skills; occupational choice; labor productivity; labor management